Properties of green composites with regenerated cellulose fiber and soybean-based thermoset for technical applications. (January 2014) - Ramamoorthy, Sunil K; Kundu, Chanchal K; Adekunle, Kayode; Bashir, Tariq; Skrifvars, Mikael
Composites were developed by reinforcing available non-woven Lyocell and viscose in acrylated epoxidized soybean oil (AESO). Compression molding was used to make composites with 40–60 wt% fiber content. The fiber content comprises only Lyocell or viscose fiber, or mixture of these fibers in known ratio. Hybrid composites were made by a mixture of both the fibers in known ratio and it affects the properties. The effect of hybridization was evident in most tests which gives us an opportunity to tailor the properties according to requirement. Lyocell fiber reinforced composites with 60 wt% fiber content had a tensile strength and modulus of about 135 MPa and 17 GPa, respectively. Dynamic mechanical analysis showed that the Lyocell fiber reinforced composites had good viscoelastic properties. The viscose fiber reinforced composites had the high percentage elongation and also showed relatively good impact strength and flexural modulus. Good fiber-matrix adhesion reflected in mechanical properties. SEM images were made to see the fiber-matrix compatibility.